The Effectiveness of Student Worksheets on HOTS in a Bilingual Classroom in Bandar Lampung - Latifah, Sri; Meisuri, Meisuri; Kesuma, Allikha Ade (Indonesian Journal of Science and Mathematics Education, 2022)
This research aims to see the effectiveness of physics worksheets on Higher Order Thinking Skills (HOTS) in bilingual classes in Bandar Lampung. The research method employed was quasi-experimental with a randomized control group pretest-posttest design. This research involved three schools, with each school having an experimental class and a control class. The independent sample t-test was performed to determine the differences in the average HOTS results of students in each class at each school. The results of the data analysis showed that there was a difference in the average HOTS of students between those who used the integrated physics worksheets in bilingual classes and the worksheets found in schools. The differences in the increased HOTS indicated that the physics worksheets in bilingual classes were effectively used.